Comparative Study to Evaluate the Width of Maxillary Anterior Teeth and Skull Circumference among Male and Female Visiting College of Dental Surgery, BPKIHS - Rai, Ankita; Suwal, Pramita; Parajuli, Prakash Kumar; Basnet, Bishal Babu; Limbu, Indra Kumar (Journal of Nepalese Prosthodontic Society, 2025)
Introduction: Restoring maxillary anterior teeth in edentulous patient without pre-extraction records is often challenging. Skull circumference has been proposed as a guide for selecting maxillary anterior teeth; however, its relationship appears to differ across gender and population. The objective of this study is to compare the width of maxillary six anterior teeth and skull circumference among males and female visiting College of Dental Surgery, BPKIHS, in eastern Nepal. Methods: Maxillary anterior teeth width and skull circumference of 470 participants (235 males and 235 females) above 18 years were measured using digital Vernier caliper and measuring tape, respectively. Mann-Whitney U test, Kruskal-Wallis test and Spearman’s correlation test were applied to assess gender and ethnic differences and correlations, respectively. Results: Significant gender difference was found in the width of six maxillary anterior teeth (p<0.001) and skull circumference (p<0.001). Across ethnic/caste group, only skull circumference differed significantly (p=0.011). Tooth width correlated with skull circumference in the total population (r=0.26, p<0.001) and in females (r=0.18, p=0.005). Conclusion: Maxillary anterior teeth width and skull circumference vary with gender and ethnicity. Skull circumference can be used as a reliable guide for selecting anterior teeth in edentulous Nepalese populations.